Post ionized defect engineering of the screen-printed Bi2Te2.7Se0.3 thick film for high performance flexible thermoelectric generator. (January 2017) - Kim, Sun Jin; Choi, Hyeongdo; Kim, Yongjun; We, Ju Hyung; Shin, Ji Seon; Lee, Han Eol; Oh, Min-Wook; Lee, Keon Jae; Cho, Byung Jin
Abstract: Flexible thermoelectric generators (f-TEGs), fabricated by the screen printing technique, have been introduced as a semi-permanent power source for wearable and flexible electronic systems. However, the output power density of the f-TEG module is still limited due to the low ZT of the screen-printed thermoelectric (TE) film. We herein report a post ionized defect engineering process that effectively controls ionized defects and improves the ZT value of a screen-printed ternary TE film. It was found that post annealing in a forming gas ambient (4% H2 +96% Ar) can reduce the nano- and micro-bismuth oxide particles in screen-printed n-type BiTeSe films, resulting in a bismuth rich condition and creation of bismuth antisite defects. We achieved a maximum ZT of 0.90 with the screen-printed n-type BiTeSe thick film at room temperature, which is almost comparable to that of the bulk Bi2 Te2.7 Se0.3 and is a 2-fold increase over the same screen-printed film without the hydrogen ambient annealing. To demonstrate the applicability of this approach, a f-TEG device with 72 TE pairs (p-type Bi0.5 Sb1.5 Te3, forming gas annealed n-type Bi2 Te2.7 Se0.3 ) was fabricated by the screen printing technique. The device generated a high output power of 6.32 mW cm −2 at ΔT=25.6 °C. These results demonstrate the feasibility of high performance and large-scale f-TEG fabrication using ionized-defect engineering. Graphical abstract: Highlights: A post ionized defect engineering process for improving ZT value of the screen-printed BiTeSe thick film is proposed. A post annealing in a forming gas ambient (4% H2 + 96% Ar) can reduce the nano- and micro-bismuth oxide particles in screen-printed BiTeSe films, resulting in a bismuth rich condition and creation of bismuthantisite defects. A maximum ZT of 0.90 with the screen-printed BiTeSe film at room temperature, which isalmost comparable to that of the bulk Bi2 Te2.7 Se0.3 and is a 2-fold increase over the same screen-printed film without the hydrogen ambient annealing. A f-TEG device with 72 TE pairs (p-type Bi0.5 Sb1.5 Te3, forming gas annealed n-type Bi2 Te2.7 Se0.3 ) generatesa high output power of 6.32 mWcm -2 at ΔT = 25.6 °C.